Human Encephalitis Complicated With Ocular Symptoms Associated With Pseudorabies Virus Infection: A Case Report - Yue, Liu; Yi, Li; Fei, Tong; MengWu, Tian; Man, Li; LiQing, Wang; YueLi, Zou; JiaLiang, Duan; Hui, Bu; JunYing, He (Frontiers in Neurology, 2022)
Pseudorabies virus (PRV) is an alpha herpesvirus found in many wild and domestic animals, and causes neurological diseases in humans. Several cases of PRV-induced human encephalitis accompanied with severe visual impairment have been reported. There is currently no effective treatment for severe visual impairment caused by PRV. We report a case of PRV encephalitis with severe visual impairment. The diagnosis and treatment experience of this patient is summarized to improve the awareness of clinicians. We present a 42-year-old man with PRV infection who was admitted due to intermittent fever for 5 days and unconsciousness for 1 day. He subsequently developed severe visual impairment during hospital stay. Empirical antiviral treatment with ganciclovir and sodium foscarnet was started on the day of admission and continued for > 50 days, which had significant treatment effect. Eye complications caused by PRV infection have been frequently reported in patients with PRV encephalitis. In this patient, based on the patient's condition, antiviral therapy was initiated on admission day, and according to the results of the next-generation sequencing of the cerebrospinal fluid, the duration of antiviral therapy was prolonged, which improved treatment efficacy and alleviated neurological symptoms and eye vision damage. To the best of our knowledge, this is the first report that describes partial restoration of acute vision loss associated with PRV infection after aggressive treatment. Our experience suggests that although prompt treatment cannot prevent the acute vision loss associated with PRV infection, timely anti-viral and anti-inflammatory treatment can alleviate ocular complications.